Parallel Computing in Local Area Networks - Tinetti, Fernando Gustavo (2004)
In this thesis, parallel computing on installed local area networks (LAN) is focused, analyzing problems and possible solutions taking into account the main factors of computing and communications. More specifically, LAN are characterized as parallel computers in the context of linear algebra applications, proposing parallelization guidelines which are: specific for parallel computing on LAN, and simple enough to be applied to a wide range of problems